The Effect of Personnel Competency and Work Environment on the Level of Effectiveness of the Safety Management System (Sms) Mediated with Compliance with Safety Procedures on Vessels Owned By Pt. Lautan Jaya Hasana - Nindyaningrum, Fitria Rasdiana; Rachman, Abdul; Rosmayana, Rosmayana (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of personnel competency and work environment on the effectiveness of the Safety Management System (SMS) mediated by safety procedure compliance on PT. Lautan Jaya Hasana's ships. The main issue raised in this research is the low level of compliance by ship crew members with safety procedures, as well as the suboptimal implementation of SMS, which impacts the operational safety of the ships. This study employs a quantitative approach with an explanatory research design. The population in this research consists of 83 ship crew members of PT. Lautan Jaya Hasana, with a sample selected using purposive sampling technique. Primary data were obtained through the distribution of questionnaires measuring respondents' perceptions of personnel competency, work environment safety, safety procedure compliance, and SMS effectiveness. Data analysis was performed using Structural Equation Modeling (SEM). The results show that personnel competency and work environment safety have a positive and significant impact on safety procedure compliance. Furthermore, safety procedure compliance was found to significantly influence the effectiveness of SMS. These findings emphasize the importance of enhancing personnel competency and improving work environment conditions to increase compliance with safety procedures, which ultimately leads to the effectiveness of Safety Management System (SMS) implementation on the ships. This study provides practical contributions to safety management in the maritime sector and enriches the empirical body of knowledge on the implementation of safety management systems in the shipping industry